Subverting Women’s Subjugation in West African Society: The Roles of Popular Music - Olusola , Kayode (Journal of Gender and Power, 2022)
Women’s subjugation is a common phenomenon especially in African society. This is due to numerous factors which including religion, culture among others. This has facilitated scholars to document literature relating to gender equality in African society. Within the frame- work of Feminist theory, this paper discusses the issue of women’s subjugation in West African societies and the roles played by popular musicians and their music in subverting this phenomenon. The methodology includes oral interviews, the textual analysis of the selected discography and the review of relevant literature. Findings reveals that text of the selected songs campaign against misconception and intimidation of women by the society, gender equality to social life, regard for women, motivation for gender equality, financial empowerment and better life for women and gender equality for Political leadership role. This paper concludes that apart from the fact that music is an ubiquitous phenomenon which covers every aspect of lives of the African people, popular music, being an integral part of popular culture of a society, has been used as an impactful medium through which women’s subjugation in different West African societies have been subverted to an extent. This is because of its high rate of patronage and ability to reach larger number of audience through the mass media. The paper therefore recommends that government through the Federal Ministry for Women’s Affairs and other corporate organizations for women’s liberation should partner with popular musicians in creating awareness and promoting the campaign against women’s subrogation the West African society.